PERANCANGAN PLTS ATAP DI GEDUNG GRAHA SEWAKA DHARMA - Agus Januar Ariawan, I Gede; Dwi Giriantari, Ida Ayu; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i03.p2, 2021)
The utilization of renewable energy can be a solution to support the supply of electrical energy, one of which is the use of solar energy with rooftop solar panels. In this study, the roof of the Graha Sewaka Dharma Building was used as a location for the design of rooftop solar power plants to be able to help with electrical energy needs and support government programs in developing the use of solar energy. The total roof area of Graha Sewaka Dharma Building is 1,616.37 m2. This design uses a battery-free On-grid PLTS system using a Solaria PowerXT- 400R-PM solar module with a capacity of 400 Wp and a Ginlong Solis S5-GC36K-LV inverter with a capacity of 36 kW. This design will calculate the capacity of solar modules that can be installed and the electrical energy produced with the limitation of the roof area and load profile in the Graha Sewaka Dharma Building. Based on the results of the study, the capacity of the rooftop PLTS installed in the Graha Sewaka Dharma Building is 188.8 kWp with a total of 472 solar module units and 6 inverter units. The energy output produced per year (energy yield) is 306,2 MWh/year. The investment feasibility study using the methods Net Present Value, Profitability Index, and Discounted Payback Period shows that this design investment is feasible. Further research is recommended to study the impact of reducing carbon emissions on the use of the PV grid.